Use of the Instagram Hashtags #winemom and #momjuice Among Mothers During the COVID-19 Pandemic: Descriptive, Cross-sectional Study - Basch, Corey H (JMIR Pediatr Parent, 2021)
BACKGROUND: The tendency of parents to consume alcohol during the COVID-19 pandemic is likely to be moderated by pandemic-related stress combined with the ongoing demands of childcare and home-based education, which are reported to be more burdensome for females than males. OBJECTIVE: The purpose of this study was to describe alcohol-related content posted by mothers on Instagram during the COVID-19 pandemic. METHODS: Using two popular hashtags, #momjuice and #winemom, 50 Instagram posts on each were collected from the “top posts” tab. The coding categories were created inductively and were as follows: displays alcohol (drinking/holding alcohol or alcohol itself), person is making alcoholic beverages, type of alcohol featured or discussed, highlights anxiety and/or depression/mental state, highlights struggling (in general), highlights parenting challenges, encourages alcohol consumption, discourages alcohol consumption, features a person wearing clothing or shows products promoting alcohol, promotes alcohol rehabilitation, highlights caffeine to alcohol daily transition throughout the day, and highlights other drugs besides caffeine and alcohol. RESULTS: Overall, the 100 selected posts had a total of 5108 comments and 94,671 likes. The respective averages were 51.08 (SD 77.94) and 946.71 (SD 1731.72). A majority (>50%) of the posts reviewed encouraged alcohol consumption (n=66) and/or displayed alcohol (n=56). Of the 66 that encouraged and/or displayed alcohol, the common type of alcohol discussed or featured was wine (n=55). Only 6 posts discouraged alcohol use and only 4 provided the audience with a disclaimer. None of the videos promoted or endorsed alcohol rehabilitation in any way. Only 37 posts highlighted struggle. However, these posts garnered more than a majority of the likes (n=50,034, 52.3%). Posts that showed struggle received an average of 1359.57 (SD 2108.02) likes. Those that did not show struggle had an average of 704.24 (SD 1447.46) likes. An independent one-tailed t test demonstrated this difference to be statistically significant (P=.0499). CONCLUSIONS: The findings of this investigation suggest that though these hashtags ostensibly exist to valorize excess alcohol consumption, they may be serving as a support system for mothers who are experiencing increased burdens and role stress during the pandemic. Given the strains placed on mothers overall and especially during the COVID-19 pandemic, efforts must be taken to increase access to and affordability of telehealth-based mental health care.